Kosakata Lagu Daerah Banyuwangi: Kajian Etnolinguistik Etnik Using - Imam Suyitno (Humaniora, 2008)
The Banyuwangi folksongs, which from theoretical perspective are an expression of the culture of Using people. The folksongs are cultural product of the Using ethnic, which is a result of the interaction of the Using people with their natural and social-cultural surroundings. As a cultural product, the utterance of this folksongs has distinct characteristics. The variety of vocabulary in an utterance reflects the dynamics on communication and social life of its speakers. The differences of cultural content in the vocabulary of the utterance are caused by the differences in the strategy of adaptation and perception pattern of the people towards the natural and social-cultural environment. For a language which does not have hierarchy of register, the utterance style of that language is used by its speakers as politeness strategy to distinguish the social classes in speech.